2015
DOI: 10.1186/s12889-015-1407-0
|View full text |Cite
|
Sign up to set email alerts
|

Common risk factors for chronic non-communicable diseases among older adults in China, Ghana, Mexico, India, Russia and South Africa: the study on global AGEing and adult health (SAGE) wave 1

Abstract: BackgroundBehavioral risk factors such as tobacco use, unhealthy diet, insufficient physical activity and the harmful use of alcohol are known and modifiable contributors to a number of NCDs and health mediators. The purpose of this paper is to describe the distribution of main risk factors for NCDs by socioeconomic status (SES) among adults aged 50 years and older within a country and compare these risk factors across six lower- and upper-middle income countries.MethodsThe study population in this paper draw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 36 publications
(35 reference statements)
10
93
2
1
Order By: Relevance
“…Being sedentary was found to impact the quality of life, which is consistent with other studies: for example, in older individuals, even light-intensity physical activity is related to higher self-rated physical health and psychosocial well-being [42]. Notably, the prevalence of a low level of physical activity in the South Africa data was higher than in any other SAGE country (China, Ghana, India, Mexico, Russian Federation) [43]. Although age and diabetes conspire to decrease fitness and strength, physical activity interventions improve functional status in older adults with and without diabetes [44].…”
Section: Discussionsupporting
confidence: 86%
“…Being sedentary was found to impact the quality of life, which is consistent with other studies: for example, in older individuals, even light-intensity physical activity is related to higher self-rated physical health and psychosocial well-being [42]. Notably, the prevalence of a low level of physical activity in the South Africa data was higher than in any other SAGE country (China, Ghana, India, Mexico, Russian Federation) [43]. Although age and diabetes conspire to decrease fitness and strength, physical activity interventions improve functional status in older adults with and without diabetes [44].…”
Section: Discussionsupporting
confidence: 86%
“…13 Another study found a higher risk for hypertension among people with higher income and residence in urban areas. 14 These findings are in contrast to multiple studies from the United States providing evidence that women of higher SES are less likely to be obese or develop diabetes, likely because of better access to health care and healthy dietary patterns, whereas lower SES women were more likely to be obese, diabetic, and hypertensive. 1519 This contrasting pattern of association between SES and health may be due to the relatively recent economic transition in countries like Ghana, because studies of other developing countries have revealed a pattern of an initial increase in overnutrition and sedentary lifestyles as a result of urbanization, preceding a later shift to increased recreational physical activity and healthy dietary patterns as the negative health consequences become apparent.…”
Section: Introductioncontrasting
confidence: 82%
“…Out of this number, 41 met the inclusion criteria for addition to the review. Two (2) additional studies were retrieved through reference screening of selected papers bringing the total number of studies included in the review to 43 [4486]. These 43 studies (Table 1) involved a sample population of 48,966 with individual study sample size ranging from 59 to 9215.…”
Section: Resultsmentioning
confidence: 99%
“…These 43 studies (Table 1) involved a sample population of 48,966 with individual study sample size ranging from 59 to 9215. The studies were conducted across all the 10 regions of Ghana and included 4 nationally-sampled studies [60, 70, 76, 86]. Regional-based studies were distributed as follows; Ashanti (n = 11), Greater Accra (n = 15), Northern (n = 7), Volta (n = 1), Upper East (n = 1), Central (n = 3) and one inter-regional study (Greater Accra and Upper West).…”
Section: Resultsmentioning
confidence: 99%